2021
DOI: 10.1111/jmcb.12802
|View full text |Cite
|
Sign up to set email alerts
|

The Collateral Costs of Clearing

Abstract: The Collateral Costs of ClearingWe study three generic clearing arrangements in the presence of two-sided limited commitment: simple bilateral clearing, segregated collateral clearing through a third party, and-most sophisticated-central counterparty (CCP) clearing. Clearing secures the settlement of obligations from overthe-counter forward contracts that smooth the income of risk-averse traders. Clearing requires collateral to guarantee settlement; this is costly, as it reduces income from investment. More so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It has been suggested that post-GFC policies ushered in a new age of central banking (see, e.g., Goodhart, 2010), a shift that precludes a return to the pre-GFC framework (Monnet, 2021). To account for evolutions and new challenges-notably environmental ones-some argue for a need to abandon the dominance of monetary over fiscal policies, and to develop a coherent framework to address the decarbonization challenge.…”
Section: Debates and Potential Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that post-GFC policies ushered in a new age of central banking (see, e.g., Goodhart, 2010), a shift that precludes a return to the pre-GFC framework (Monnet, 2021). To account for evolutions and new challenges-notably environmental ones-some argue for a need to abandon the dominance of monetary over fiscal policies, and to develop a coherent framework to address the decarbonization challenge.…”
Section: Debates and Potential Limitationsmentioning
confidence: 99%
“…Others hold that the relevant challenge is not to replay "an old debate about whether central banks should be independent, but rather to define this independence in new terms" (Monnet, 2021). Instead, focusing on the euro area, Monnet (2021) calls for the creation of a European Credit Council that would operate under the authority of the European Parliament.…”
Section: Debates and Potential Limitationsmentioning
confidence: 99%
See 2 more Smart Citations